The Institutional Alumni Survey (IAS): A Measure of Graduate Performance & Program Quality - Linda Deloney; Shelly Lensing; Elizabeth Hicks; James Clardy (MedEdPORTAL, 2013)
Abstract Introduction ACGME-accredited programs are required to monitor and track graduate performance, but few measures exist beyond board certification examinations. As alumni surveys have been identified as an indicator of the caliber of a program, the Institutional Alumni Survey (IAS) was developed as an additional measure. Postgraduation reflection on one's education, especially in comparison to graduates from other programs, provides a unique assessment of program quality. Graduates who have recently entered practice are able to compare and contrast their training with the realities of medical practice and national standards. The IAS is a GME tool to collect data from physicians who are recent graduates of ACGME-accredited residency and fellowship programs, regardless of medical specialty. Methods The IAS is a self-assessment tool designed for online administration using a commercially available survey sponsor. It measures satisfaction with preparation for practice, adequacy of training, general competence, career satisfaction, and pursuit of nonclinical activities such as teaching and research. Two subscales compose this measure: (1) Preparedness & Training Adequacy, and (2) Confidence & Support. Four free-text questions are included to encourage candid comments about program strengths and weaknesses and to solicit suggestions for improvement. The survey can be completed in approximately 15 minutes. Results Over a 4-year period, the IAS proved to be feasible, cost-effective, and an efficient use of resources. Pooled response data increase the potential for valid and reliable results from the IAS. Internal reliability using Cronbach's alpha was good for the subscales (0.83 and 0.73). Construct validity included use of an expert panel and relating the subscales to the overall career satisfaction question. Discussion The IAS has supported program directors who have limited time and resources to develop new assessment tools. When the sponsoring institution provides the human and technical resources to conduct the survey and report the results, programs needed only to provide a list of targeted alumni with contact information. Descriptive data generated by the IAS during an annual institutional survey can identify training strengths and areas for improvement and inform the educational program improvement process at both the program and institutional levels. The IAS also may function as a tool for institutional oversight, providing tracking data, and evidence of longitudinal quality improvements.